1996
DOI: 10.1111/j.1432-1033.1996.00716.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Biological Activity of Chemically Modified Nisin A Species

Abstract: (Received 21 May112 August 19Y6) -EJB 96 074213Nisin, a 34-residue peptide bacteriocin, contains the less common amino acids lanthionine, p-methyllanthionine, dehydroalanine (Dha), and dehydrobutyrine (Dhb). Several chemically modified nisin A species were purified by reverse-phase HPLC and characterized by two-dimensional NMR and electrospray mass spectrometry. Five constituents, [2-hydroxy-AlaS]nisin, [Tle4-amide,pyruvyl-Leu6Jdes-Dha5-nisin, [Met(0)2l]nisin, [Ser33]nisin, and nisin-(I -32)-peptide amide, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…These results are principally in agreement with the work published by Rollema et al [30] who reported chemical stability of nisin A at 20, 37, and 75 ∘ C in various buffers at pH range from 2 to 8. The nisin stability after 3 months of storage at 20…”
Section: Testing Of Thermal Long-term Stabilitysupporting
confidence: 83%
“…These results are principally in agreement with the work published by Rollema et al [30] who reported chemical stability of nisin A at 20, 37, and 75 ∘ C in various buffers at pH range from 2 to 8. The nisin stability after 3 months of storage at 20…”
Section: Testing Of Thermal Long-term Stabilitysupporting
confidence: 83%
“…In the upper part of the intestinal tract (duodenum and ileum), the nisin concentrations estimated by ELISA were approximately 10-fold higher than those estimated by the bioassay, while in fecal samples, the difference was around 200-fold (Table 2). This indicates that degradation or inactivation of nisin occurs in the GI tract, since proteolytic fragments of nisin will be detected in the competitive ELISA (3), while a nearly intact nisin molecule is needed to retain biological activity (25). Nisin is reported to undergo proteolytic degradation mediated by the pancreas enzyme ␣-chymotrypsin present in the GI tract (10).…”
Section: Discussionmentioning
confidence: 99%
“…a) Schematic representation of the photocatalytic modification of nisin; b) MALDI‐TOF measurement of the crude product of the photocatalytic modification of nisin with 2 a I) degraded Nisin(CH 2 OPhOMe) 2 due to water addition followed by hydrolytic cleavage of the C‐terminal region,13 II) Nisin(CH 2 OPhOMe) 2 , III) Nisin(CH 2 OPhOMe) 3 .…”
mentioning
confidence: 99%